PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO BERBASIS ANIMASI MATA KULIAH ILMU BAHAN BANGUNAN DI PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA - Muhammad Ridwan Apriansyah (Jurnal Pensil : Pendidikan Teknik Sipil, 2020)
Abstract This research is research Research and Development (R & D) and research development model Hannafin & Peck. This research is basically done 3 phases,Need to implement Phase, Design Phase, and the Development and Implementation Phases. This research use the question form as a tool for testing the feasibility of media through a media expert and expert validation materials as well as the assessment of students.Learning media product development results in the form of nine video animation. The assessment by media expert get the value of the 83.01% categorized strongly agree is used as a tool in the learning process as well as the variations of the media learning courses on the science of building materials. Assessment by expert material get value of 82.03% categorized strongly agree is used for learning the science of building materials to make it easier to understand. Learning media assessment of video-based animation on a test class by students get value of 89.00% categorized for easy use strongly agree the students understand the material and effectively reduce the saturation on the process learning courses science of building materials.